Agricultural trade and development: A value chain perspective - Miet Maertens; Johan Swinnen (World Trade Organization (WTO), 2015)
The system of global agricultural and food trade is undergoing rapid processes of change, with important implications for economic development. In this paper we document and discuss these changes; including the rapid growth and structural change in agri-food trade, the increased consolidation in food supply chains, the proliferation of public and private food standards, high and volatile food prices, and increased vertical coordination in the chains. We investigate what the implications are of these changes for developing countries, for their participation in international agricultural trade as well as for economic development, income mobility and poverty reduction in rural areas.
Keywords: F13; L14; O19; O24; Q17; Q18; 330; global food supply chains; vertical coordination; food standards; food prices; developing countries